(untitled) (Международный научный журнал «Инженер», 2026)
This article analyzes the environmental and economic problems of fly ash and aggregates, which are waste coal fuel at thermal power plants (TPP), as well as the possibilities of their effective use in the production of building materials. The article analyzes the use of fly ash in concrete and cement, methods for improving its physical, chemical and mechanical properties, based on scientific research and foreign patents. In order to save resources in construction and protect the environment, special attention is paid to the technologies for processing TPP waste and their efficiency. At the same time, based on the applied methodology, geological surveys and experimental tests, methods for preparing concrete and blocks based on fly ash are recommended